Associated Determinants Between Evidence of Burnout, Physical Activity, and Health Behaviors of University Students - Souza, Rafael Octaviano de; Ricardo Guilherme, Flavio; Elias, Rui Gonçalves Marques; dos Reis, Lucas Lopes; Garbin de Souza, Otavio Augusto; Robert Ferrer, Miquel; dos Santos, Sérgio Luiz Carlos; Osiecki, Raul (Frontiers in Sports and Active Living, 2021)
Risk behaviors and signs of burnout are associated with substantial health losses and university dropouts. Physical activity can be an effective approach to reduce these factors. The objective of this study was to analyze aspects related to health behaviors, physical activity, and signs of burnout in university students and their association with physical activity. The probabilistic cluster sample consisted of 3,578 regularly enrolled undergraduate students from UFPR in Curitiba, based on a population sample of 24,032 university students. The students completed the MBI-SS and NCHA II instruments. Descriptive statistics were used to identify demographic indicators and characteristics of the university environment. For the proportion of subjects with respective confidence intervals (CI = 95%), contingency tables involving the chi-square test (χ2) were used. The prevalence of signs of burnout was estimated in punctual proportions accompanied by the respective confidence intervals (CI = 95%). To analyze the associations between the independent variables and signs of burnout, the Hierarchical Logistic Regression was used through an analysis adjusted by the other independent variables involved in the models (CI = 95%). Results showed that the prevalence of individuals who showed signs of burnout was 40.4%. The hierarchical multiple regression model pointed to: female sex (OR = 1.30; 1.11–1.51); age between 20–24 years (OR = 1.51; 1.25–1.83); and 25–29 years (OR = 1.69; 1.27–2.24); being single (OR = 2.67; 1.01–7.10); presenting regular/poor health perception (OR = 1.59; 1.13–2.22), belonging to Human Sciences courses (OR = 1.37; 1.14–1.64); attending 2nd or 3rd year (OR = 1.34; 1.12–1.61); poor academic performance (OR = 5.35; 4.11–6.96); mean (OR = 2.08; 1.78–2.43). We conclude that academics showed a high prevalence of health risk behaviors and correlate and diagnose emotional problems and signs of burnout. Signs of burnout were significantly associated with the practice of physical activity in its three dimensions; however, in the adjusted analysis for demographic indicators, the characteristics of the university environment, and health behaviors, physical activity was not significant for the model.